Ivermectin Poisoning with Neurological Manifestations in 10 Years Old Girl - A Case Report - Syed Sajid Hussain shah; Bibi Aalia (Gandhara University, 2022)
In developing countries, accidental poisoning is a serious public health problem in children. But unintentional poisoning by parents in the form of medication is very rare. Ivermectin belongs to the group of Avermectins and is used in veterinary medicine and in use for human parasitic diseases. We report the case of 10 years old girl given ivermectin by her mother for an unspecified amount. The patient presented to the hospital with seizures and remained in a coma for five days. The patient was managed symptomatically and discharged home in stable condition with parents' counselling regarding child safety.